التدريب في الملاعب الاصطناعية الخشنة وعلاقته بالإصابات التي يتلقاها عدائي ألعاب القوى - نمرود, بشير (Université de M'sila, 2018)
المستخلص: تتمحور الدراسة حول مختلف الإصابات التي يتلقاها عدائي ألعاب القوى أثناء التدريب في الأرضيات الخشنة سواء كانت التدريبات تنافسية أو ترفيهية أو صحية والتعرض لمختلف أنواع الإصابات والأسباب المؤدية إليها؛ كما اعتمد في هذا البحث على المنهج الوصفي الذي تضمن تحليل وتفسير النتائج المحصل عليها تبعا للاختبارات اللازمة بما في ذلك قانون التناسب واختبار كاف تربيع؛ استخدم الباحث الاستبيان كأداة لجمع المعلومات كما دعمت هذه الدراسة خلفية نظرية تمثلت في المراجع المعتمد عليها Abstract : The study centering on various injuries received by athletics during training in hard floors, whether competitive, recreational, health training and exposure to different types of injuries and the reasons leading to it; also adopted in this research on the descriptive approach which included the analysis and interpretation of the results obtained depending on the necessary measures, including tests the law of proportionality and adequate square test; the researcher used the questionnaire as a tool to gather information, as this study has supported the theoretical background was the references relied upon.
Keywords: الكلمات الدالة: التدريب.- الملاعب الاصطناعية الخشنة.- الإصابات الرياضية. Key words: training.- hard synthetic playgrounds.- sports injuries.